The Trends of Online Reference Choice in Postgraduate Students of FKIP UNIB as a Source of Reference in Writing Scientific Works - Hamzah, Syukri; Hadiwinarto, Hadiwinarto; Kurniawan, Rio; Lestari, Neta Dian (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
This study aims to reveal the tendency of online reference choices used by Postgraduate students of FKIP UNIB in writing scientific papers. The research method used is the descriptive method. The reachable sample in this study totaled 221 people consisting of 38 third-graduate students and 183 second-graduate students. The collection was carried out using an online questionnaire with Google Forms media and interviews. The results of the study show that in general online journals occupy a very dominant position as references in writing scientific papers. The tendency of its use as a reference is more as a theoretical reference than as a fact, supporting or strengthening research results written in scientific papers. From a language standpoint, journals in Indonesian (L1) tend to be the preferred reference source in writing various types of scientific papers. The driving factors for this are limitations in mastering foreign languages and the desire to quickly complete studies.